The reality of organizational communication in Yemeni sports federations - aziz alqudaimi, (sports creativity, 2025)
This study aims at identifying the grounds of organizational communication in the Yemeni sports federations. It also aims at publishing an on-ground image for the level of organizational communication in these federations, identifying how seamless the flow of information is within the organizational structure of such federations, establishing appropriate ways for correcting deviation or processing obstacles, if any, in order to achieve the objectives of organizational communication inside sports federations. Randomly selected from the Ministry of Youth and Sports and the headquarters of the Yemeni sports federations in the capital Sana'a, a field study was conducted on a sample of (140) individuals, including leaders, members, and managers for ten sports federation, all for this purpose. Dates range from 16 - 07 - 2017 through 19 - 09- 2017, the questionnaire was used to collect data and information that consisted of (24) phrases and descriptive approach. After previewing and analyzing the data of the field study, we came out with the following results: The level of organizational communication in the Yemeni sports federations is good and effective. Organizational communication plays an effective role in the flow of information through the Yemeni sports federations.